2021
DOI: 10.1021/acs.jctc.1c00067
|View full text |Cite
|
Sign up to set email alerts
|

Localized Active Space Pair-Density Functional Theory

Abstract: Accurate quantum chemical methods for the prediction of spin-state energy gaps for strongly correlated systems are computationally expensive and scale poorly with the size of the system. This makes calculations for many experimentally interesting molecules impractical even with abundant computational resources. In previous work, we have shown that the localized active space (LAS) self-consistent field (SCF) method is an efficient way to obtain multi-configuration SCF wave functions of comparable quality to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…In our previous, work we have used this flexibility to change S and M S for specific subspaces to model ground and excited spin states of the molecule. 21,38 For example, the ferromagnetic and anti-ferromagnetic coupling of locally high-spin (quintet) Fe [II] 21 This requires the generation of symmetry adapted molecular wave functions as linear combinations of multiple LAS states.…”
Section: Lasscfmentioning
confidence: 99%
“…In our previous, work we have used this flexibility to change S and M S for specific subspaces to model ground and excited spin states of the molecule. 21,38 For example, the ferromagnetic and anti-ferromagnetic coupling of locally high-spin (quintet) Fe [II] 21 This requires the generation of symmetry adapted molecular wave functions as linear combinations of multiple LAS states.…”
Section: Lasscfmentioning
confidence: 99%
“…On the theoretical side, one strategy is to identify subspaces of the CAS that can be treated on different footings 26,27 or interact with one another only weakly [28][29][30][31][32] . The localized active-space self-consistent field (LASSCF) method [33][34][35][36] , also known as the cluster mean-field (cMF) method, 37 is an example of such a strategy. LASSCF is designed for applications in which electrons are strongly correlated in different weakly interacting physical regions of a molecule and approximates the strongly correlated part of the wave function as a single antisymmetrized product of subspace wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the authors have recently shown that LASSCF accurately reproduces the CASSCF spin-state energy gaps of bimetallic compounds and the simultaneous dissociation of two double bonds in bisdiazene at a significantly reduced cost 34,35 . However, LASSCF fails to recover any electron correlation between fragments, for example in the cis-trans isomerization of stilbene and similar systems 36 . Moreover, methods to restore the missing correlation variationally 38 , perturbatively 37,39 , or via the coupled-cluster (CC) approach 40 on classical computers must usually enumerate a general many-body basis for each fragment.…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical side, one strategy is to identify subspaces of the CAS that can be treated on different footings 26,27 or interact with one another only weakly [28][29][30][31][32] . The localized active-space self-consistent field method (LASSCF) is an example of such a strategy [33][34][35][36] . LASSCF is designed for applications in which electrons are strongly correlated in different weakly interacting physical regions of a molecule and approximates the strongly correlated part of the wave function as a single antisymmetrized product of subspace wave functions.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the authors have recently shown that LASSCF accurately reproduces the CASSCF spin-state energy gaps of bimetallic compounds and the simultaneous dissociation of two double bonds in bisdiazene at a significantly reduced cost 34,35 . However, LASSCF fails to recover any electron correlation between fragments, for example in the cis-trans isomerization of stilbene and similar systems 36 . Moreover, because the wave function of each fragment is a general manybody wave function, it is not straightforward 10,37 to apply traditional perturbative or truncated coupled-cluster (CC) corrections based on second quantization 38,39 on top of a LASSCF reference to recover the missing correlation, at least on classical computational hardware.…”
Section: Introductionmentioning
confidence: 99%